World Bank Group Joint Projects : A Review of Two Decades of Experience - Independent Evaluation Group (World Bank, Washington, DC, 2017)
Working as One World Bank Group is central to the WBG’s strategy of helping countries end extreme poverty and promote shared prosperity sustainably. Over the past 20 years (1995 to 2015), many initiatives have sought to boost WBG effectiveness by increasing the number of projects jointly financed by IFC, MIGA, and/or the World Bank. Yet the number of joint projects still amounts to a very modest share of the overall WBG project commitments. This first systematic stocktaking by IEG of joint or co-financed projects within the WBG offers insight on both benefits of, and challenges in, developing, structuring, supervising, monitoring and evaluating joint projects. It draws lessons from past experience, staff and client feedback, and highlights implications for WBG management regarding expectations of increased co-financed projects in the future.